COVID- 19 and its Impacts on Project Management (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: There have been various types of research and literature written to describe the impact of COVID-19 on business and the supply chain. However, data regarding the impact of the COVID-19 situation especially on project management has been very limited. The paper will attempt to reduce the literature gap by discussing the impact of COVID-19 on project management. Where we relied on a conceptual framework that uses COVID-19 as the independent variable and project management as the dependent variable, we used theoretical empirical research methods we collected data from a variety of sources, including online government documents and articles…etc. Through this, we concluded that the impact of COVID-19 significantly on the project management was negative, which caused the interruption of operations and unavailability of supplies and caused the restructuring. However, it has taught project management teams and other stakeholders some significant lessons including the importance of planning, flexibility, and collaboration.keywords: covid-19,Project management, strategy